Enhancing first-attempt success in radial artery cannulation: a PDCA-driven approach for anesthesiology residency training - Zhang, Meng; Zhao, Shuchuan; Bai, Fangjing; Yu, Shanshan; Zhou, Huixian; Song, Siyuan; Xu, Guangmin (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of the Plan-Do-Check-Act (PDCA) cycle in improving the first-attempt success rate of radial artery cannulation among anesthesiology residents undergoing standardized training.MethodsEighty-six residents from Sichuan Provincial People's Hospital, comprising 70 anesthesiology and 16 non-anesthesiology residents, were randomly divided into a control group and a PDCA group, each with 43 participants. Key outcomes assessed included first-attempt success rate, procedure duration, ultrasound utilization, preparation errors, and complication rates.ResultsIn anesthesiology residents, the PDCA group achieved a significantly higher first-attempt success rate (94%, 31/33) compared to the control group (43%, 16/37; P < 0.001). Among non-anesthesiology residents, the PDCA group also outperformed the control group, with success rates of 80% (8/10) vs. 33% (2/6; P = 0.048). Procedure duration was notably shorter in the PDCA group for both anesthesiology residents (median: 0.80 min, IQR: 0.50–2.30) and non-anesthesiology residents (median: 1.50 min, IQR: 0.70–3.00), compared to the control group (4.10 min, IQR: 3.10–5.90, and 3.70 min, IQR: 2.50–5.00; P < 0.001 and P = 0.026, respectively). Additionally, ultrasound usage was higher in the PDCA group, and assessment scores showed improvement, though the latter did not reach statistical significance.ConclusionThe PDCA cycle significantly enhances the first-attempt success rate and efficiency of radial artery cannulation while promoting greater adoption of ultrasound. These findings highlight its value in advancing standardized training for anesthesiology residents.